Enamel daily secretion rates of deciduous molars from a global sample of children. (December 2021) - McFarlane, Gina; Loch, Carolina; Guatelli-Steinberg, Debbie; Bayle, Priscilla; Le Luyer, Mona; Sabel, Nina; Nava, Alessia; Floyd, Bruce; Skinner, Mark; White, Sophie; Pitfield, Rosie; Mahoney, Patrick
Abstract: Objective: To investigate and describe the variation in enamel daily secretion rates (DSRs) of naturally exfoliated deciduous molars (n = 345) from five modern-day populations (Aotearoa New Zealand, Britain, Canada, France, and Sweden). Design: Each tooth was thin sectioned and examined using a high-powered Olympus BX51 microscope and DP25 digital microscope camera. Mean DSRs were recorded for the inner, mid, and outer regions of cuspal and lateral enamel, excluding enamel nearest the enamel-dentin junction and at the outermost crown surface. Results: Mean DSRs did not vary significantly between populations, or by sex. Cuspal enamel grew slightly faster than lateral enamel (mean difference 0.16 µm per day; p  < 0.001). The trajectory of DSRs remained relatively constant from inner to outer cuspal enamel and increased slightly in lateral enamel ( p  = 0.003). Conclusions: The DSRs of deciduous molars from modern-day children are remarkably consistent when compared among populations. While growth rates are faster in cuspal than lateral enamel, the trajectory of enamel formation changes only slightly from inner to outer regions. The trajectory of DSRs for deciduous molars differs to that of permanent molar enamel, which typically display a steep increase in matrix deposition from inner to outer enamel. Highlights: Daily secretion rates (DSR) reported for deciduous molars from global sample. Deciduous molar enamel DSRs show limited variation between populations. Deciduous molars show minor increase in DSRs from inner to outer enamel.